Implementation, availability and regulatory status of an OECD accepted Reconstructed Human Epidermis model in Brazil - Rodrigo De Vecchi; Vanja Dakic; Guilherme Mattos; Anne-Sophie Rigaudeau; Veronica Oliveira; Cristina Garcia; Nathalie Alépée; José Cotovio; Charbel Bouez (Fundação Oswaldo Cruz (FIOCRUZ), 2018)
Introduction: In 2014, Brazil has joined the growing list of countries to ban cosmetic products from being tested on animal models. The new legislation comes into force in 2019. As a result, the interest for validated alternative testing methods for safety assessment has been increasing in academia, industry and associations. However, the lack of specific legislation on the use of biological material of human origin for toxicological tests makes the access to alternative in vitro models difficult. Furthermore, importation to Brazil is not possible on timely manner. Method: In this article, we report the implementation process of a Reconstructed Human Epidermis (SkinEthic™ RHE), an alternative model internationally accepted by OECD, through a technology transfer from EPISKIN® Lyon to Brazil. Regulatory evolution has been motivating the implementation and wide use of alternative methods to animal testing in several industry segments including cosmetic and pharmaceutical. Results: Protocol has been shown to be robust and highly reproducible. Quality control parameters (histological analysis, barrier function test and tissue viability) were performed on 24 batches assembled in Brazil. SkinEthic™ RHE model use allows the full replacement of animal test methods for skin hazards identification. It has regulatory acceptance for several toxicological endpoints, such as the Draize test for skin irritation and corrosion. It allows the reduction and refining of pre-clinical protocols through tiered strategies. Implementation of SkinEthic™ RHE protocol is just a first and important step towards a new approach of toxicological safety testing in Brazil. Conclusion: The implementation was successfully done and reported here. However, in order to follow completely the new legislation up to 2019, the availability of validated models is essential. Quality control tests done on RHE batches produced in Brazil demonstrate that the model met OECD acceptance criteria and therefore can be used for reliable prediction of irritation and corrosion classification.